Surface Characteristics of Different Dental Cements after Incubation with Adherent and Non-adherent Strains of Streptococcus Mutans - Facury, Analia Gabriela Borges Ferraz; Thedei Júnior, Geraldo; Almeida, Rodolfo Nunes de; Moura, Marcos Boaventura de; Costa, Ana Rosa; Correr-Sobrinho, Lourenço; Borges, Gilberto Antonio (ARCHIVES OF HEALTH INVESTIGATION, 2025)
The aim of this study was to evaluate surface characteristics and Knoop hardness of two resin cements after incubation with adherent and non-adherent strains of Streptococcus mutans. The ATCC 25175 strain and a mutant isolated due to its low biofilm forming capacity and normal acidogenic capacity were used. Disks with 5 mm diameter and 2 mm thickness were fabricated with RelyX U200 and Allcem following the manufacturer’s instructions. Specimens were incubated in TSB medium with the adherent or non-adherent strains at 37ºC for 30 days, changing the culture medium every day, whereas control group specimens were incubated with sterile culture medium. Then, all specimens were subjected to microhardness Knoop. Representative specimens were examined using scanning electron microscopy (SEM). Tukey multiple comparisons test and unpaired t-test was used to compare two groups (α = 0.05). The resin cement RelyX U200 do not presented degradation or microhardness alteration under conditions tested. On the other hand, the resin cement Allcem presented more organic matrix degradation, exposing more filler particles after incubation with adherent strain than after incubation with the non-adherent strain. Microhardness of Allcem was smaller after incubation with ATCC strain than with non-adherent strain, and both presented smaller microhardness than the specimens of the control group. In conclusion, the resin cement RelyX U200 was not affected by the medium incubation with both adherent or non-adherent bacteria. The resin cement Allcem was more affected by the adherent bacteria strain then non-adherent regarding to surface topography.